Reinventing e-commerce : Amazon's bet on unmanned vehicle delivery - Walker, Russell, 1972- (SAGE knowledge. Cases., 2016)
In 2013, in an interview on American television programme 60 Minutes, Amazon CEO Jeff Bezos announced that Amazon would soon change the future of online shopping by enabling customers to receive items within 30 minutes of ordering. This delivery service, Bezos said, would be powered by unmanned autonomous drones and could be offered as soon as 2015. Still, Amazon needed some answers before it could launch autonomous delivery services. This study examines Amazon's radical plans.